The Role of Communication in Maintaining the Resilience of Muslim Families in Mandailing Natal in the Era of Disruption: A Qualitative Approach Based on Islamic Values - Elismayanti Rambe (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to determine the challenges and opportunities in building family resilience in the era of disruption. The research method used is qualitative, involving in-depth interviews with research informants using purposive sampling, non-participant observation, and documentation studies. The results of the study indicate that the high divorce rate in Mandailing Natal is mainly due to the unpreparedness of families to adapt to the rapid changes in communication technology, which has an impact on the poor quality of communication and causes family resilience to become fragile. Building the resilience of Muslim families in the era of disruption requires specific understanding and steps from various parties that can help families face the challenges and changes in society and technology so they can adapt and maintain the religious values that are the foundation of family unity.